Kolaviron prevents carbendazim-induced steroidogenic dysfunction and apoptosis in testes of rats (2013)
The study evaluated the protective role of kolaviron (an isolated biflavonoid from the seed of Garcinia kola) and vitamin E in carbendazim-induced reproductive dysfunction in male rats. Adult male Wistar rats were orally exposed to carbendazim (200 mg/kg) singly or in combi-nation with kolaviron (100 and 200 mg/kg). Exposure to carbendazim significantly decreased the activities of superoxide dismutase and catalase but markedly increased sialic acid con-centration and lipid peroxidation in the testes of rats. Western blot analysis revealed that carbendazim treatment decreased the expression of steroid acute regulatory (StAR) protein and androgen binding protein (ABP) with concomitant decrease in activities of steroido- genic enzymes. Germ cell apoptosis in carbendazim-treated rats was confirmed by TUNEL assay. However, pretreatment with kolaviron and vitamin E restored the testicular antiox- idant status and steroidogenesis and decreased apoptotic nuclei to near control level in carbendazim-treated rats. Kolaviron may prove useful in combating carbendazim-induced reproductive toxicity.